2004
DOI: 10.1021/jm049743b
|View full text |Cite
|
Sign up to set email alerts
|

Novel 5-HT7Receptor Inverse Agonists. Synthesis and Molecular Modeling of Arylpiperazine- and 1,2,3,4-Tetrahydroisoquinoline-Based Arylsulfonamides

Abstract: A series of arylpiperazine- and 1,2,3,4-tetrahydroisoquinoline-based arylsulfonamides was synthesized and evaluated for their interactions with the constitutively active 5-HT7 receptor. Effects on basal adenylate cyclase activity were measured using HEK-293 cells expressing the rat 5-HT7. All ligands produced a decrease of adenylate cyclase activity, indicative of their inverse agonism. Additionally, computational studies with a set of 22 inverse agonists, including these novel inverse agonists and inverse ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 43 publications
2
44
0
3
Order By: Relevance
“…Although there are no clinical data indicating that an inverse agonist demonstrates superior clinical efficacy over the pure antagonists, data from numerous in vitro (Dupre et al, 2004;Mahe et al, 2004;Tryoen-Toth et al, 2004;Vermeulen et al, 2004;Vertongen et al, 2004) and some in vivo studies (Bond et al, 1995;Adan and Kas, 2003;Schwartz et al, 2003) have demonstrated the potential therapeutic advantage of inverse agonists. Many clinically important medicines have been demonstrated to behave as inverse agonists when tested against either wild-type or mutated GPCRs (Milligan, 2003); we believe, to some extent, that this evidence highlights the potential advantage of inverse agonists over neutral antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no clinical data indicating that an inverse agonist demonstrates superior clinical efficacy over the pure antagonists, data from numerous in vitro (Dupre et al, 2004;Mahe et al, 2004;Tryoen-Toth et al, 2004;Vermeulen et al, 2004;Vertongen et al, 2004) and some in vivo studies (Bond et al, 1995;Adan and Kas, 2003;Schwartz et al, 2003) have demonstrated the potential therapeutic advantage of inverse agonists. Many clinically important medicines have been demonstrated to behave as inverse agonists when tested against either wild-type or mutated GPCRs (Milligan, 2003); we believe, to some extent, that this evidence highlights the potential advantage of inverse agonists over neutral antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…(17)). The 4 aligned agonists, together with 3 other less active agents (93,97,98), were then used in CoMFA study. Different combinations of steric and electrostatic fields with a lipophilic potential or logP parameter were analyzed, and it turned out that models with overlapping (a 5-hydroxyl oxygen, the centroid of an adjacent aromatic ring and a protonated nitrogen atom); as to the second, its ligand alignment was guided by the receptor binding site.…”
Section: Pharmacophore Models For 5-ht 4 R Ligandsmentioning
confidence: 99%
“…Mice were individually placed in a glass cylinder (25 cm high; 10 cm in diameter) containing 10 cm of water maintained at [23][24][25] C and were left there for 6 min. A mouse was regarded as immobile when it remained floating on the water, making only small movements to keep its head above it.…”
Section: Forced Swim (Porsolt) Test In Swiss Albino Micementioning
confidence: 99%
“…A very important class of 5-HT receptors ligands are derivatives of 1,4-disubstituted arylpiperazine ( Figure 1). Such arylpiperazine derivative with longchain substituents incorporated on the basic nitrogen of the phenylpiperazine ring -long-chain arylpiperazines (LCAPs) -are commonly studied classes of bioactive compounds [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Despite the enormous progress in central nervous system (CNS) drug discovery, particularly in the areas of mood disorders and schizophrenia, new drugs are still being sought.…”
Section: Introductionmentioning
confidence: 99%